Hydrochemistry of groundwaters from alluvial and fractured igneous aquifers at the western region of Lake Hazar (Elaz, Turkey) - Okan, Ozlem Oztekin; Guven, Atahan (Springer Heidelberg, 2019)
The study area is located at Eastern Anatolian Fault Zone and at the western shore of Lake Hazar (Elazig, Turkey). This study aims to identify the hydrochemical features of groundwaters from fractured igneous aquifers and to correlate them with the alluvial aquifer's groundwaters. The water samples were collected in April and September during the rainy and dry periods, respectively. As a result of active tectonism in this region, hard rocks have gained secondary porosity and permeability. According to major ion composition, the fractured igneous and alluvial aquifer groundwaters can be grouped into the Ca-Mg-HCO3 type, whereas the groundwaters emerging very close to the thrust fault locations can be classified as the Mg-Ca-HCO3 type. The water-rock interaction process represents the primary factor controlling the hydrochemistry of the investigated groundwaters. Generally, the alluvial aquifer's groundwaters are characterized by low pH values. Clay minerals in the alluvial material may act as H+ buffers and cause decreased pH values. According to the isotopic tracers of O-18, H-2, and H-3, the spring water discharging at higher altitudes from the fractured igneous aquifer reflects rapid circulation and recharging from recent precipitation compared to alluvial aquifer groundwater. The groundwaters' major ions fall well within the permissible limits for drinking water in Turkey. In contrast, the NO3- and NH4+ concentrations from groundwaters, especially those recharging from fractured igneous aquifers, are very close to or in excess of the limit values. The high concentrations of NO3- and NH4+ in groundwaters presumably result from landfills and the use of agricultural fertilizers in the study area. The surface waters (Lake Hazar and man-made wetland (MMW)) also are investigated within the scope of the hydrochemistry studies. Higher TDS, Cl-, and Na+ concentrations in the MMW reflect salinity that could result from lake water intrusion and evaporation processes.
Keywords: Hydrochemistry; Fractured igneous aquifer; Saturation index; Ammonium contamination; Lake Hazar; Elaz